Analysis of the effects of intellectual capital on innovation in the petrochemical industry in southern Tamaulipas, Mexico - Nahuat-Román, B.; Rodríguez-Vargas, M. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2026)
The importance of innovation in companies is widely recognized in the literature and a proposal to detonate it that has been consolidating is the use of internal knowledge-based resources. Therefore, this paper aims to analyze the effects of intellectual capital on innovation in the petrochemical industry in southern Tamaulipas, Mexico. A questionnaire was used to collect the perceptions of 64 individuals working as middle managers in 16 plants in Altamira, Tamaulipas. Subsequently, with the technique of structural equations in its variance analysis modality, it was found that intellectual capital (through the human and structural capital) positively and significantly affects process innovation, highlighting the intensity of human capital, which leads to the conclusion that to the extent that the companies analyzed manage their intellectual capital better, they will be more likely to generate process innovation. The greatest contribution of this work consists in the proposal of a tested and validated instrument for data collection, likewise, it broadens the knowledge of the effects of intellectual capital in a type of innovation scarcely addressed by the literature in Mexico.